If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(2x + -1) = 0 Reorder the terms: (-3 + x)(2x + -1) = 0 Reorder the terms: (-3 + x)(-1 + 2x) = 0 Multiply (-3 + x) * (-1 + 2x) (-3(-1 + 2x) + x(-1 + 2x)) = 0 ((-1 * -3 + 2x * -3) + x(-1 + 2x)) = 0 ((3 + -6x) + x(-1 + 2x)) = 0 (3 + -6x + (-1 * x + 2x * x)) = 0 (3 + -6x + (-1x + 2x2)) = 0 Combine like terms: -6x + -1x = -7x (3 + -7x + 2x2) = 0 Solving 3 + -7x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -2x)(3 + -1x) = 0Subproblem 1
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {0.5, 3}
| 6x-11=7x+5 | | 2z^3+z^2=15z | | 9x-7=-12 | | 3x^2-12x+9=1 | | 1a-15=48-3 | | 6x+9=29-4x | | x^2-4x=x^2-2x | | 32-11x=142 | | x^2-3x+x=x^2-2x | | 2(3x+5)=5(x-7) | | 9+a=-42 | | 54=8-j | | y=x(4-2x)(5-2x) | | 10z+3=12-7 | | y=6e-16*x^6 | | 7x^2+75x+50=0 | | 900-7x=95 | | 7T+4=4+-11 | | 4x-1.4=.6 | | Y+11=1.4(x-6) | | 3T-9=T+11 | | -Y-2X+9Y= | | 2(7x-55)=7x-20-5 | | 5x-1.9=2.6 | | 16x-7x+26= | | 2(-4+3)x=2(-2) | | 3x+145x=75 | | 5x-1.9=.6 | | 1.5d+6.75=3+2.75d | | 1-b=1 | | -2sinx+3cosx=0 | | -2sint+3cost=0 |